Expert System Detecting Automated Teller Machine (Atm) Damages At Indonesian Sharia Bank Using Naïve Bayes Method - Aminuddin Aziz; Imam Saputra; Dito Putro Utomo (Institute of Computer Science (IOCS), 2022)
Automatic Teller Machine or better known as ATM is a tool used in the banking world for cash withdrawal transactions, cash deposits, balance check transfers and for various types of bill payments made to serve customers who can operate 24 hours a day without the service of a person. teller. However, Automatic Teller Machine (ATM) is very susceptible to damage and it takes a long time to find out the damage. Naïve Bayes is a method for generating parameter estimates by combining various available information from samples and other information that has been previously available and has a high success rate of calculation by taking a statistical approach to inference and induction on classification problems which uses conditional probability as the basis. Based on the results of the application of the expert system algorithm, the Naive Bayes Method is suitable for designing a damage detection system for ATM machines, the system built can help Indonesian Sharia Banks in Diagnosing ATM machine damage using the Naïve Bayes Method.